STUDI PENURUNAN KADAR COD (CHEMICAL OXYGEN DEMAND) MENGGUNAKAN FERRI KLORIDA (FeCl3) PADA LIMBAH CAIR TAPIOKA DI DESA NGEMPLAK MARGOYOSO PATI - Diana Islamawati; Yusniar Hanani Darundiati; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The tapioca industry produces liquid waste with COD levels that exceed the standard of 300 mg/l. COD level in tapioca liquid waste was 14,444 and 8,519.6 mg/l. Therefore, it was necessary to wastewater treatment, one of them with coagulation-flocculation system using ferric chloride coagulant. The purpose of this study was to determine the decrease in COD levels after being treated using coagulant ferri chloride in tapioca liquid waste. This type of research was quasi experimental research with pretest posttest study design with control group. The sampel in this research was part of waste water tapioca produced by UD Sumber Makmur in the final shelter that flows into the river. Total sample for treatment (20 gr, 25 gr, 30 gr, 35 gr, and 40 gr) with 5 replication was 35 samples. Data analysis used Kruskal Wallis test showed that there was difference average in decreasing COD level of tapioka liquid waste with various dose of ferric chloride (p-value= 0.004). The result of Man Whitney test, showed that groups between dose variation that have significant difference in decreasing COD level of tapioca liquid waste (p≤0.05) was control group with all treatment groups and 20 gr with 40 gr group treatment. COD level after treatment decreased gradually as the dose of ferric chloride was added. The decrease occurred in the control group was 4,827.3 mg/l (43.3%), dose of 20 gr/l was 8,221.6 mg/l (73.8%), dose of 25 g/l was 8,757.3 mg/l (78.6%), dose of 30 gr/l was 9,043.0 mg/l (81.2%), dose of 35 gr/l was 9,544.6 mg/l (85.7%), and dose of 40 gr/l was 9,942.1 mg/l (89.2%). The greatest decrease presentage was at a dose of 40 gr/l with a decrease from COD level 11,136.2 mg/l to 1,194.1 mg/l or 89.2%. There was a decrease in COD levels using ferric chloride but the COD levels produced were still above the established quality standard.